Riding and Thriving on the API Hype Cycle. - Vukovic, Maja; Laredo, Jim; Muthusamy, Vinod; Slominski, Aleksander; Vaculin, Roman; Wei Tan; Naik, Vijay; Silva-Lepe, Ignacio; Kumar, Arun; Srivastava, Biplav; Branch, Joel W. (Communications of the ACM, 2016)
The authors reflect on challenges encountered by enterprises in investing on application programming interface (API) ecosystems. Topics covered include the evolution of the service-oriented architecture (SOA) concept into Web-friendly technologies, API availability according to the free online API registry called ProgrammableWeb and identified factors that made API ecosystems successful. They discuss abundance of API choice, API exposure, and API consumability.